The Update of Fetal Growth Restriction Associated with Biomarkers - Liqun Sun; Dandan Shi (Wolters Kluwer Health, 2022)
Abstract. Fetal growth restriction (FGR) has a prevalence of about 10% worldwide and is associated with an increased risk of perinatal mortality and morbidity. FGR is commonly caused by placental insufficiency and can begin early (<32  weeks) or in late (≥32  weeks) gestational age. A false positive antenatal diagnosis may lead to unnecessary monitoring and interventions, as well as cause maternal anxiety. Whereas a false negative diagnosis exposes the fetus to an increased risk of stillbirth and renders the pregnancy ineligible from the appropriate care and potential treatments. The clinical management of FGR pregnancies faces a complex challenge of deciding on the optimal timing of delivery as currently the main solution is to deliver the baby early, but iatrogenic preterm delivery of infants is associated with adverse short- and long-term outcomes. Early and accurate diagnosis of FGR could aid in better stratification of clinical management, and the development and implementation of treatment options, ultimately benefiting clinical care and potentially improving both short- and long-term health outcomes. The aim of this review is to present the new insights on biomarkers of placenta insufficiency, including their current and potential value of biomarkers in the prediction and prevention for FGR, and highlight the association between biomarkers and adverse outcomes in utero to explore the specific mechanism of impaired fetal growth that establish the basis for disease later in life.